Surprising acidity for the methylene of 1,3-indenocorannulenes? - Shi Liu; Märt Lõkov; Sofja Tshepelevitsh; Ivo Leito; Kim K. Baldridge; Jay S. Siegel (Beilstein Journal of Organic Chemistry)
Quantitative assessment of the first acidity constant (pKa) for BFC (27.6 in CH3CN) and FIC (27.8 in CH3CN) shows the methylene protons to be significantly more acidic than those in related cyclopentadiene (32 in CH3CN), indene (34 in CH3CN), or fluorene (37 in CH3CN) and comparable to the methine of 9-perfluorophenylfluorene (28.14 in CH3CN). This work reports quantitative pKa values of BFC and FIC, places those values in a broadened context of CpH-cognate hydrocarbon acidity and presents a Clar–Loschmidt graph perspective to help understand the “surprises”.